2015
DOI: 10.3758/s13428-015-0600-5
|View full text |Cite
|
Sign up to set email alerts
|

PsiMLE: A maximum-likelihood estimation approach to estimating psychophysical scaling and variability more reliably, efficiently, and flexibly

Abstract: A simple and popular psychophysical model-usually described as overlapping Gaussian tuning curves arranged along an ordered internal scale-is capable of accurately describing both human and nonhuman behavioral performance and neural coding in magnitude estimation, production, and reproduction tasks for most psychological dimensions (e.g., time, space, number, or brightness). This model traditionally includes two parameters that determine how a physical stimulus is transformed into a psychological magnitude: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…In order to account for the heteroscedasticity inherent in the w and age data (i.e. accuracy and w values are more variable in younger children), the normally distributed regression error was allowed to scale with 1/Age (see also Odic, Im, Eisinger, Ly, & Halberda, in press). The best‐fitting parameters are shown in Figures and and in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In order to account for the heteroscedasticity inherent in the w and age data (i.e. accuracy and w values are more variable in younger children), the normally distributed regression error was allowed to scale with 1/Age (see also Odic, Im, Eisinger, Ly, & Halberda, in press). The best‐fitting parameters are shown in Figures and and in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The reference dot quantity either contained 25, 30, or 39 dots, which correspondingly induced overestimation, linear-like estimation, and underestimation in participants' performance . Third, there are individual differences in the underestimation bias in adults Odic et al, 2015) and young children who have acquired symbolic number knowledge (Libertus, Odic, Feigenson, & Halberda, 2016). Altogether, these behavioral findings suggest that people are able to map between the ANS and SNS, but that this mapping is not precise and is subject to a systematic underestimation bias.…”
Section: The Mapping Between the Approximate Number System And The mentioning
confidence: 89%
“…More critically, previous research found that people tend to underestimate large quantities in nonsymbolic number estimation tasks (Crollen, Castronovo, & Seron, 2011;Krueger, 1982;Odic, Im, Eisinger, Ly, & Halberda, 2015). For example, when presented with 60 dots, people more commonly estimate fewer than 60 dots in contrast to estimating more than 60 dots.…”
Section: The Mapping Between the Approximate Number System And The mentioning
confidence: 91%
See 2 more Smart Citations